KELAYAKANFLASHCARD MATERI KEANEKARAGAMAN HAYATI DARI BUAH AROK BESAR, AROK KECIL, DAN TINGOH - Khairiyah, Siti; Daningsih, Entin; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to determine the feasibility of flashcard media on biodiversity material of class X high school from morphology and nutritioned content as wellfruit fiber ofarok besar (Ficus variegata Blume), arok kecil (Ficus variegata Blume), and tingoh (Daemonorops melanochaetes). Some information from the results of morphological analysis and nutritioned content was implemented in flashcard learning media. This research was descriptive method using purposive sampling technique with two stages, namely instrument validation and media validation. Instrument validation was carried out by two biology education lecturers and one high school biology teacher who taught class X. The media validation was carried out by five validators consisting of two biology education lecturersand three high school biology teachers. Data were analyzed by lawshe method with CVR and CVI formulas. Based on the results of instrument validation using a questionnaire with five aspects consisting of twelve criteria, the questionnaire was feasible to be used and corrected, while for media validation obtained the CVR and CVI value of 0.99 which corresponded toLawshe's minimum CVR value for five validators,so the flashcard mediawas declared valid and wasfeasible to use as a biodiversity material learning media for class X high scholl. Keywords : Flashcard, Biodiversity, Arok besar, Arok kecil, Tingoh.